Pemetaan Lokasi Penerapan Nature-Based Solution Melalui Pendekatan Berbasis Masyarakat Sebagai Mitigasi Bencana Tanah Longsor di Kecamatan Ngebel - Agus Joko Pitoyo; Irbah, Amanda; Anindya Hias Bestari; Sulistiawan Fajar Nugroho (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Topographically, Ngebel Sub-district, Ponorogo Regency is located in the western highland complex of Mount Wilis which is steep so that many landslides occur. This prompted an analysis of the vulnerability of landslides in Ngebel sub-district. This study formulates solutions for landslide disasters using Nature-based Solutions (NbS) or nature-based solutions in landslide-prone areas in Ngebel District by involving the community so that they can find the most suitable location for the application of NbS. NbS is a step to be able to implement mitigation in the Ngebel District area. The implementation of this service is carried out using several methods, including literature studies, secondary data collection, data processing, and counseling to the community. Information on the results of the FGD and landslide vulnerability mapping information is taken into consideration in determining alternative solutions, in the form of NbS. NbS selected for landslide disaster mitigation in Ngebel District in the form of vegetative measures and bio-engineering techniques. The selection of NbS is based on things that support the sustainability of agricultural, plantation, and livestock potential in Ngebel District so that existing solutions are able to utilize the potential and community involvement.